Novel insights into chloroplast genome evolution in the green macroalgal genus Ulva (Ulvophyceae, Chlorophyta) - Liu, Feng; Chen, Nansheng; Wang, Hongshu; Li, Jiamin; Wang, Jing; Qu, Fan (Frontiers in Plant Science, 2023)
To understand the evolutionary driving forces of chloroplast (or plastid) genomes (plastomes) in the green macroalgal genus Ulva (Ulvophyceae, Chlorophyta), in this study, we sequenced and constructed seven complete chloroplast genomes from five Ulva species, and conducted comparative genomic analysis of Ulva plastomes in Ulvophyceae. Ulva plastome evolution reflects the strong selection pressure driving the compactness of genome organization and the decrease of overall GC composition. The overall plastome sequences including canonical genes, introns, derived foreign sequences and non-coding regions show a synergetic decrease in GC content at varying degrees. Fast degeneration of plastome sequences including non-core genes (minD and trnR3), derived foreign sequences, and noncoding spacer regions was accompanied by the marked decrease of their GC composition. Plastome introns preferentially resided in conserved housekeeping genes with high GC content and long length, as might be related to high GC content of target site sequences recognized by intron-encoded proteins (IEPs), and to more target sites contained by long GC-rich genes. Many foreign DNA sequences integrated into different intergenic regions contain some homologous specific orfs with high similarity, indicating that they could have been derived from the same origin. The invasion of foreign sequences seems to be an important driving force for plastome rearrangement in these IR-lacking Ulva cpDNAs. Gene partitioning pattern has changed and distribution range of gene clusters has expanded after the loss of IR, indicating that gene transfer was more extensive and more frequent in Ulva plastomes, which was markedly different from that in IR-containing ulvophycean plastomes. These new insights greatly enhance our understanding of plastome evolution in ecologically important Ulva seaweeds.